PREVALENCE OF NON-COMMUNICABLE DISEASE RISK FACTOR AMONG THE ADULT POPULATION OF BHARATPUR METROPOLITAN CITY, CHITWAN, NEPAL - Shrestha, Niki; Shah, Sanjeeb; Khanal, Gayatri; Ghimire, Prabha (Journal of Chitwan Medical College, 2024)
Background: Non-communicable diseases (NCDs) are the leading causes of disease burden worldwide. The data from Nepal indicated 6% increase in the deaths caused by non-communicable diseases from 2014 to 2018. The nationwide STEPS survey of non-communicable disease risk factor, 2019 showed high prevalence of risk factors, posing a greater threat for the NCD epidemic in future in the country. Thus, this study aims to find out the prevalence of non-communicable disease risk factors among the adult population of Bharatpur Metropolitan City in Chitwan, Nepal. Methods: A descriptive, community-based cross-sectional study was conducted among 310 respondents residing in Bharatpur Metropolitan. Four wards were selected purposively and convenient sampling was used to select the sample. A semi-structured questionnaire based on WHO NCD STEPS instrument adapted to the local context, was used to collect the data. A descriptive analysis was carried out to analyze the data. Results: The prevalence of current smoking, alcohol consumption, low intake of vegetables and fruits, raised salt intake and low physical activity was found to be 18.1%, 38.7%, 94.6%, 80% and 66.5% respectively. Regarding metabolic risk factors, the prevalence of ever-raised blood pressure, blood sugar and cholesterol was 50%, 28.4% and 17.4% respectively. Conclusions: The study revealed a high prevalence of behavioral and metabolic risk factor which varied in the age group of 40-60 years. The findings call for population specific policy and interventions and focused actions for the behavior modification through primary prevention module and behavior change communication strategy.